PEMIKIRAN TAFSÎR MESIR MODERN J.J.G JANSEN (Telaah atas Karya J.J.G.Jansen The Interpretation of The Koran in Modern Egypt) - Abu Bakar Abu Bakar (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2011)
Abstract: Jansen is a researcher that classifies the work of interpretation (tafsîr) into: firstly, an interpretation adopting a modern science but not oppose against the holy Quran, it is called tafsîr al-‘ilmî. Secondly, an interpretation that is designed to help reader understand the holy Quran or philological interpretation (al-tafsîr al-lughawî). Thirdly, an interpretation dealing with the Muslim deed and it is called practical interpretation (tafsîr al-adabî al-ijtimâ’î). Jansen is about to display a short description that covers the answers of explanation inadequacy of the previous researchers’ studies. He mainly clarifies the history of interpretation and western studies on interpretation developing in Islamic world. As a matter of fact, Jansen’s view is majorly a kind of beginning critical of his attention on interpretation. He focuses the research object on the interpretation of Muhammad Abduh, then he compares it to the other intrepretations that are considered up to standard to be classified into his work of interpretation. Key Words: al-Qur’ân, tafsîr, dan Jansen